2021
DOI: 10.7150/jca.52993
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscape of PI3K-AKT-mTOR Pathway in Breast Cancer: Implications for Targeted Therapeutics

Abstract: Background: Comprehensive analysis of PI3K-AKT-mTOR pathway gene alterations in breast cancer may be helpful for targeted therapy. Methods: We performed targeted sequencing using a panel of 520 cancer-related genes to investigate gene alterations in the PI3K-AKT-mTOR pathway from 589 consecutive Chinese women diagnosed with stage I-III breast cancer. Analyses of overall survival (OS) were performed using the publicly available clinical and genomic data from METABRIC. Results: PI3K-AKT-mTOR pathway gene alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…PIK3CA mutations were found in only 2 of 14 evaluated male BC cases that is lower than previously reported by our group in women with BC[ 19 , 20 ]. Piscuoglio et al [ 2 ] sequenced 241 genes in 59 male BC and found that most recurrent mutations affected the PIK3CA gene (20%).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…PIK3CA mutations were found in only 2 of 14 evaluated male BC cases that is lower than previously reported by our group in women with BC[ 19 , 20 ]. Piscuoglio et al [ 2 ] sequenced 241 genes in 59 male BC and found that most recurrent mutations affected the PIK3CA gene (20%).…”
Section: Discussioncontrasting
confidence: 73%
“…However, these rates would be lower than their female counterparts that have been detected in approximately 30%-40% of female BC[ 21 ]. In vitro and translational research in tumor samples from clinical trials found that PIK3CA mutations reduce sensitivity to anti-HER2 drugs[ 22 ] and endocrine modulation[ 19 , 20 ]. Additionally, a recent study demonstrates that Alpelisib, a drug targeting the PIK3CA pathway, has activity in breast cancer cases with presence of the mutation[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signalling pathway is particularly relevant due to its central role in cell growth, proliferation, survival, motility, metabolism, and immune response [ 103 , 104 ]. Alterations and hyperactivation of the PI3K/AKT/mTOR pathway are observed in many cancers, with estimations that aberrations are present in 60–70% of breast cancers [ 103 , 105 , 106 ]. The observation that somatic alterations in receptor tyrosine kinase (RTK; e.g., HER, FGFR receptors), RAS [e.g., neurofibromatosis type 1 (NF1)] and PI3K/AKT/mTOR (e.g., AKT1) pathways occur at higher frequency in endocrine resistant/metastatic disease compared with primary disease highlight the importance of these growth processes in endocrine resistance [ 102 ].…”
Section: Molecular Characterization Of In Vitro Mo...mentioning
confidence: 99%
“…Strategies to overcome tumor hypoxia adaptation include disrupting HIF signaling, suppressing TME acidosis, mediating metabolism and targeting hypoxic tumor cells pathways [ 20 , 21 ]. As a key point to tumor anabolism, mTOR is mainly activated by phosphatidylinositol-3 kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) signal [ 22 ], which also regulates HIF-1α translation [ 23 , 24 ]. Meanwhile, mTOR is a therapeutic target for tumors due to the function in promoting the synthesis of amino acids, glucose and other substances required for cancer cell growth, enabling tumors metastasis and anti-apoptosis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%